2007
DOI: 10.1111/j.1463-1318.2007.01400.x
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal amelanotic melanoma

Abstract: Early diagnosis is key for efficient treatment and improved survival rate for patients with this unusual variant of melanoma. There is no difference in terms of age, time of diagnosis, stage and survival between pigmented and amelanotic anorectal melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 8 publications
0
49
0
1
Order By: Relevance
“…According to the literature, most frequently mentioned complaints are rectal bleeding and/or anorectal pain and they were also observed in our patients. Hence, the initial symptom at presentation may be bleeding and therefore, melanomas are commonly mistaken for haemorrhoidal disease [7,[11][12][13]. In our studies, the final diagnosis was confirmed by positive biopsy in two cases preoperatively and in two patients postoperatively.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…According to the literature, most frequently mentioned complaints are rectal bleeding and/or anorectal pain and they were also observed in our patients. Hence, the initial symptom at presentation may be bleeding and therefore, melanomas are commonly mistaken for haemorrhoidal disease [7,[11][12][13]. In our studies, the final diagnosis was confirmed by positive biopsy in two cases preoperatively and in two patients postoperatively.…”
Section: Discussionmentioning
confidence: 52%
“…Anorectal melanoma is not pigmented in about 30% of cases and amelanotic malignant melanomas may resemble a villous carcinoma [11]. However, anorectal melanoma may be also similar to cutaneous melanoma for which the stage of the disease and tumour thickness is the main prognostic factors [2].…”
Section: Discussionmentioning
confidence: 99%
“…It is more common in women, and more than half to 3 quarters of patients in case series are female. 4,6,22,24,27 Weinstock 24 reports an incidence of 1.7 cases per 1 million population per year in the United States. Statistical estimates from Europe 21 and Asia 28 are in a similar range.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the vast majority of series note that about a quarter of patients have amelanotic disease. 1,6,25,27 The exact prognostic significance of a lack of pigmentation in AM is unclear, and no published report has compared pigmented lesions with amelanotic lesions. However, after combining epidemiological, histopathological, and follow-up data from 4 centers, Hillenbrand and colleagues 27 conclude that survival is most probably comparable between both types of AM.…”
Section: Pathology and Histologymentioning
confidence: 99%
See 1 more Smart Citation